Prinsip Qoulan Maysuro dalam Ceramah Gus Iqdam Perspektif Tfsir Asyarowi - Firdaus, Salsabil Fadilah; Pinanditha, Senja Elling; Qolbiyah, Syifaul; Islam, Muhammad Syamsuddinil; Aziz, Moh Ali; Yaqin, Ainul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research examines the principles of qaulan maysura in Gus Iqdam's lectures through the Tafsir Asy-Sya'rawi approach, with a focus on its relevance and application in contemporary da'wah. Qaulan maysura or